(untitled) (Journal of Dhaka Medical College, 2010)
This cross sectional study was carried out at Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of November 2008 to April 2009 on patients who received fresh frozen plasma. Relevant information of those patients was noted from the records kept at the Department of Transfusion Medicine. The collected data was statistically analyzed. In this study it was observed that 939 units of FFP were required in BSMMU during study period. 289 patients required these units of FFP. The age of the patients that required FFP ranged from 1 day to 75 years. Among them highest 99 (34.25%) were in the age group1 day to. 10 years. There were178 (61.59%) males and 111 (38.41%) females. Out of 289 patients 111 (38.41%) was B+ve, 86 (29.76%) was O+ve, 66 (22.84%) was A+ve and 26 (08.99%) was AB+ve. According to Rh typing maximum unit 930 (99.04) units were Rh D +ve, 9 units (00.96%) were Rh D-ve. Highest number of FFP Unit 329 (35.04%) was used in day care center in transfusion medicine department. Followed by Gastro-enterology 188 (20.02%), Burn & Plastic surgery 140(14.91%), Paediatrics & allied 106 (11.29%), Rest 176 units by other departments. According to clinical indication highest number of FFP Unit 271 (28.86%) was used for Hemophilia A, followed by CLD 210 (22.36%), Burn140 (14.91%). Distribution of the units of FFP according to rational use it was found that a large number of unit 386 (41%) use was not clinically justified. Study shows 60 (20.77%) patients was not supplied with correct documentation. According to requirement Transfusion Medicine alone uses 35%, other dept of university uses 46%, 19% of unit is supplied to other medical centers. Key words: Fresh frozen plasma; Transfusion; Clinical audit. DOI: 10.3329/jdmc.v18i2.6273 J Dhaka Med Coll. 2009; 18(2) : 132-135